Low-rise Residential Complexes of PetersburgPetrograd-Leningrad of 1900-1941 Period Peculiarities of a New Residential Planned Unit Formation - Padma Priya, M; Periasamy, J K; Jayaselvi, P; Siddharth, R Aditya (International Journal of Psychosocial Rehabilitation, 2019)
The blind person is assisted while shopping so that they can buy quality products and are not misled by false claims or discounts. Here we propose a camera-based system that is used to help blind people read text patterns printed on objects. To obtain the object from the background and extract the text pattern from that object, the system captures the image from the camera and then detects the object region. Also, a recommendation system is built, which helps to choose the right product based on customer reviews. Customer reviews can give an idea about the quality of the product; reviews are collected from online websites and a Sentiment analysis algorithm is used to analyze the review of the product recognized